2021
DOI: 10.37939/jrmc.v25i4.1763
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Nasal Foreign Bodies and Their Presentation in Paediatric Age Group

Abstract: Objectives: To observe the relationship of nasal foreign bodies in terms of patient’s age as well as the type of foreign body and removal technique. Materials and Methods: This retrospective cross-sectional study was conducted in ENT department, Akbar Niazi Teaching Hospital, Islamabad from April 2017 to May 2018. A total of 120 patients selected by non-probability consecutive sampling technique with inclusion criteria of all children less than 12 years with foreign body in nose were recruited for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Previous study carried out at the tertiary treatment facilities in Pakistan, had demonstrated that for the 3,570 hospital admitted patients, 27% had gastroenterological pathologies, 68% had decompensated chronic liver disease (DCLD) and 10% had reported cases for liver disease with DCLD at 92% in the emergency ward. 7 From January to December 2009, a prospective study in 95 patients was carried out. The most prevalent cause of cirrhosis in the study was HCV infection (61.66%), followed by HBV, hepatitis B and C virus coinfection, and hepatitis B and D virus superinfection in 18.94%, 5.3% and 4.2% patients respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study carried out at the tertiary treatment facilities in Pakistan, had demonstrated that for the 3,570 hospital admitted patients, 27% had gastroenterological pathologies, 68% had decompensated chronic liver disease (DCLD) and 10% had reported cases for liver disease with DCLD at 92% in the emergency ward. 7 From January to December 2009, a prospective study in 95 patients was carried out. The most prevalent cause of cirrhosis in the study was HCV infection (61.66%), followed by HBV, hepatitis B and C virus coinfection, and hepatitis B and D virus superinfection in 18.94%, 5.3% and 4.2% patients respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were categorized into stages of ACLF. 7 Treatment was given to all the patients as per the stan-dard guidelines; however, a liver transplant was offe-red to only those patients who met the criteria for this procedure during the visit of the foreign transplant team to our hospital. Data collected included demo-graphics, underlying liver disease, precipitating fac-tors, stage of ACLF, etc.…”
Section: Introductionmentioning
confidence: 99%